An Examination of the Role of Public Libraries Addressing Social Inclusion in India - Nanjunda, D. C. (Journal of Information and Knowledge, 2017)
The major objectives of libraries are not just providing books. In today’s world, the public library has a vital responsibility in providing services to all excluded groups in the society. This study examines the actual services provided by the public libraries to support social inclusion of different communities. This study was conducted using questionnaires in selected libraries in south Karnataka districts. This study has found lack of sufficient awareness about the role of libraries in inclusive development, and a lack of training, among the library staff towards different social inclusion aspects in the studied public libraries. Some of the social inclusion related services like employment information ; information for farmers, special services for senior citizens, training for competitive examinations, SC/ST cell, health information, awareness about community development programmes, awareness about various Govt. schemes are not being frequently provided in any of the studied libraries. Also libraries are facing shortage of fund. The Government also should provide enough autonomy and funds for such special activities.